Bicentennial Project of the Independence of Peru: The branderization of the national community? - Mejía Contreras, Andrea (2020)
This essay proposes to analyze the national community within the framework of the Bicentennial Project of the Independence of Peru. To achieve this, at first, we will briefly present what is the Bicentennial Project. In a second part, we will analyze the mandates proposed from this special project by the central Government. Specifically, the flags of values and the moments of celebration proposed by the project. In the third part, we intend to analyze which national community is being configured from these mandates. This will be done from the analysis of the confluence of three paradigms of construction of the national community (modernist-classical, post-colonial and branding) and the analysis of what it implies to promote a successful community that aims to configure the peruvian State. Finally, we will reflect on the limitations of this project and its national community proposal. For the elaboration of the present article, we will make the revision of legal norms of the peruvian State, the web page of the Bicentennial Project and some journalistic notes that address the matter.